Peran Antioksidan terhadap Radikal Bebas pada Periodontitis - Louisa, Marie; Tjhie, Shirley (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Periodontitis is a chronic inflammation of periodontal tissue. The progression of periodontitis depends on the immune response and host vulnerability. Studies have demonstrated oxidative stress as part of periodontal pathogenesis. Oxidative stress is a condition that occurs when there is an imbalance between free radical levels and antioxidants. Objectives: This literature review aims to give an overview of free radicals and antioxidants in periodontal disease. Literature Reviews: Antioxidants act as part of the host defense that neutralize free radicals. Antioxidants are not only important for inhibiting oxidative stress and tissue damage, but also important in preventing the increased production of pro-inflammatory cytokines, which results from persistent activation of the host defense response. Conclusion: Periodontal condition can be affected by endogenous antioxidant levels. Because of its important role, exogenous antioxidants should be added to complement endogenous antioxidants. Natural exogenous antioxidants can be obtained from certain foods.